Analogue Rice as The Vehicle of Public Nutrition Diversity - Noviasari, Santi; Widara, Suba Santika; Budijanto, Slamet (KEMAS: Jurnal Kesehatan Masyarakat, 2017)
Analogue rice is artificial rice product made from non-rice raw material by extrusion technique, which can be the vehicle of public nutrition diversity. The objectives of this research were to formulate and characterize analogue rice made from of sorghum, mocaf and other additional material. The method of analogue rice production is by twin screw extruder hot extrusion done in 2013. The research steps were the formulation of analogue rice, sensory evaluation to choose the best formula, and physico-chemical characterization of the best formula. The best two samples that were chosen are analogue rice made from 30% sorghum flour, 15% cornstarch, and 15% arenga starch (analogue rice B) and analogue rice made from 30% mocaf and 30% cornstarch (analogue rice F). Analogue rice B has 21.72% of amylose (medium) with 4% of dietary fiber while analogue rice F has low amylose which is 14.49%, make it more sticky, with 4.21% of dietary fiber.